2013
DOI: 10.1093/nar/gkt286
|View full text |Cite
|
Sign up to set email alerts
|

Stability of RNA quadruplex in open reading frame determines proteolysis of human estrogen receptor α

Abstract: mRNAs encodes not only information that determines amino acid sequences but also additional layers of information that regulate the translational processes. Notably, translational halt at specific position caused by rare codons or stable RNA structures is one of the potential factors regulating the protein expressions and structures. In this study, a quadruplex-forming potential (QFP) sequence derived from an open reading frame of human estrogen receptor α (hERα) mRNA was revealed to form parallel G-quadruplex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 53 publications
1
58
0
Order By: Relevance
“…Moreover, the presence of G4 motifs in the human estrogen receptor alpha (hERalpha) mRNA has been demonstrated to affect the correct folding of hERalpha and its proteolysiss (36). Certain anti-prion drugs have been described that inhibit PFAR and diminish prion misfolding (33).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the presence of G4 motifs in the human estrogen receptor alpha (hERalpha) mRNA has been demonstrated to affect the correct folding of hERalpha and its proteolysiss (36). Certain anti-prion drugs have been described that inhibit PFAR and diminish prion misfolding (33).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from intergenically occurring quadruplexes, four-stranded motifs also occur in open reading frames (ORFs). Sugimoto and colleagues described the influence of G-quadruplexes occurring in proteincoding sequences (Endoh et al, 2013a(Endoh et al, , 2013b(Endoh et al, , 2013cEndoh and Sugimoto, 2013). It seems that quadruplex formation increases the potential of inducing ribosomal stalling and frameshifting (Murat et al, 2014;Yu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, HEG modification is valuable for the efficient destabilization of TBA by pressure approach. Furthermore, it has been demonstrated that G-quadruplex formation inhibits the reaction of transcription and translation, which results in generation of different product of transcripts and proteins [15,16]. Thus, the applications to control G-quadruplex-mediated gene expressions such as transcription and translation are quite valuable.…”
Section: Resultsmentioning
confidence: 99%